2018
DOI: 10.1021/acs.jpcc.8b03952
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrothermally Synthesized Cubic-Structured BaTiO3 Ceramic Fillers on Ionic Conductivity, Mechanical Integrity, and Thermal Behavior of P(VDF–HFP)/PVAc-Based Composite Solid Polymer Electrolytes for Lithium-Ion Batteries

Abstract: Solid polymer electrolytes (SPEs) with high ionic conductivity and wide electrochemical window are highly desirable for all-solid-state rechargeable lithium batteries. Herein, we report the use of hydrothermally derived nano-BaTiO3 (BT) as nanofillers in poly­(vinyl acetate)/poly­(vinylidene fluoride–hexafluoro propylene) and its use as composite SPE (CSPE) for Li-ion batteries. The CSPE was prepared by the solution casting technique and lithium bis-trifluoromethanesulfonylimide is used as salt. The molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 66 publications
0
14
0
1
Order By: Relevance
“…The addition of silver nanoparticles was found to enhance the mechanical properties of the polymer and also retarded crack propagation and fracture behavior, and thus improved the durability of the denture base. A similar strategy for the same application was also reported by Sasikumar et al [130] who prepared CSPE using BT, PVAc/poly(VDF-co-HFP) and lithium bistrifluoromethanesulfonylimide (LiTFSI) as the salt (Fig. 37).…”
Section: Applicationsmentioning
confidence: 72%
See 2 more Smart Citations
“…The addition of silver nanoparticles was found to enhance the mechanical properties of the polymer and also retarded crack propagation and fracture behavior, and thus improved the durability of the denture base. A similar strategy for the same application was also reported by Sasikumar et al [130] who prepared CSPE using BT, PVAc/poly(VDF-co-HFP) and lithium bistrifluoromethanesulfonylimide (LiTFSI) as the salt (Fig. 37).…”
Section: Applicationsmentioning
confidence: 72%
“…Results show that compared with ceramic free SPE, the conductivity was increased to reach a value of 2 x 10 -3 Scm -1 at ambient temperature. Moreover, it was found that in the case of CSPE permission of [130] Copyright 2018 American Chemical Society.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…4a, b), suggesting that less triflate-containing anions were in pairs in the ANF-based electrolytes [68]. The intensity of the peak at around 1631 cm −1 with respect to the LiTFSI aggregation [67] also decreased greatly. On the basis of the elemental electronegativity values, FTIR analyses and reports from other researchers [62][63][64], we can easily deduce that the hydrogen bond interactions between the -NH groups in ANF and the TFSI − anions (mainly the F atoms, because of the high F electronegativity and the F-related peak intensity change) resulted in the effective dissolution and dissociation of LiTFSI, which would increase the free ion concentration (C i ).…”
Section: Ion Conductancementioning
confidence: 96%
“…Η μπαταρία είναι μια διάταξη, η οποία μετατρέπει τη χημική ενέργεια σε ηλεκτρική μέσω μιας ηλεκτροχημικής οξειδοαναγωγικής αντίδρασης. Συγκεκριμένα, κατά τη φόρτιση, τα δύο ηλεκτρόδια συνδέονται με μια εξωτερική πηγή ηλεκτρικού ρεύματος και η ενέργεια που δίνεται στο σύστημα αποθηκεύεται στη μπαταρία με τη Παράλληλα, έχει μελετηθεί αρκετά η χρήση του συμπολυμερούς PVdF-HFP (88:12) ως πολυηλεκτρολύτη [190,191], ενώ μια πιο πρόσφατη μελέτη αναφέρει ότι το συμπολυμερές PVDF-HFP/PVA με BaTiO3 [192] παρουσιάζει ιοντική αγωγιμότητα 2 mS cm -1 . Κάποια άλλα συστήματα που έχουν μελετηθεί, περιλαμβάνουν ηλεκτρολύτες από γέλη πολυμερούς (gel polymer electrolytes, GPEs) που βασίζονται σε υβριδικές μεμβράνες με ιονικά υγρά με ιοντικές αγωγιμότητες πάνω από 6 mS cm -1 στους 30 ο C και καλή ηλεκτροχημική σταθερότητα σε δυναμικό πάνω από 5.0 V [193].…”
Section: γενική επισκόπησηunclassified